The traces of the cult of St. Raymond of Penyafort in the preaching of Fabian Birkowski. A contribution to studies on the Dominicans’ hagiographic writings in Old Poland - Maria Rowińska-Szczepaniak (Folia Historica Cracoviensia, 2024)
St. Raymond of Penyafort is not contemporarily a well-known figure in Poland. Neither was he in the days of Old Poland, when he enjoyed popularity only within rather narrow circles. Without a doubt, in that period he was known in the environment of scholars connected with the Faculty of Law of Cracow Academy, where the chair dealing with his compilation of The Decretals of Gregory IX, stipulated in the foundation act issued already by Casimir III the Great, survived until the reform introduced by Hugo Kołłątaj (the second half of the 18th century). If he was regarded as an outstanding legal theorist in the circle of lawyers, he was worshipped as a saint primarily in the Order of Preachers, the third General in the history of which he had been. The evidence of the presence of his cult among the Dominicans are, among others, the two texts of Fabian Birkowski, OP, a Baroque preacher, which are discussed in this article. They are Kazanie na dzień S. Raymunda [A sermon for the Feast Day of St. Raymond] included in the collection Kazania na święta doroczne [Sermons for Annual Holidays] (Cracow 1620) and the Latin speech under the title S. Raymundus sive mare liberum Sanctis, from the collection Orationes ecclesiasticae (Cracow 1622). In both texts, while making a presentation of the figure of St. Raymond, the preacher concentrated his attention on the Saint’s crossing the sea between Majorca and Barcelona on his Dominican’s cape. The miracle attributed to the Saint made for Birkowski the starting point for further considerations which – in the case of the sermon – concerned the spiritual light, whereas in that of the Latin oration – the missionary’s activity of the Church and in particular – Dominicans’ missions. In the sermon devoted to St. Raymond, the preacherappears as a theologian, skillfully making use of various quotations from the Bible and theological literature. In turn, the oration reveals his potential of an experienced erudite, skillfully combining biblical motifs with elements drawn from the literature of Greek-Roman antiquity. The comparative analysis of the texts confirms the Maria Rowińska-Szczepaniak, The traces of the cult of St. Raymond of Penyafort… 41 particular character of the collection Orationes ecclesiasticae in the output of Father Birkowski, encouraging scholars to conduct further studies on the speeches included in it, as well as on their place in the literature written in Latin in the days of Old Poland.